Securing SQL server protecting your database from attackers - Cherry, Denny (Syngress, 2015)
Annotation
Previous edition: 2012
Includes bibliographical references and index
Keywords: SQL server; COMPUTERS / Internet / Security; COMPUTERS / Networking / Security; COMPUTERS / Security / General; Database security